THE EFFECT OF FLIPPED CLASSROOM ON COLLEGES’ WRITING ABILITY OF DESCRIPTIVE TEXT FOR THIRD SEMESTER AT UNIVERSITY OF HKBP NOMMENSEN PEMATANGSIANTAR PEMATANG SIANTAR - Siahaan, Basar Lolo; Siahaan, Sanggam; Situmeang, Siska; Gurning, Yuliska (Dharmas Education Journal (DE_Journal), 2025)
The purpose of this research is to find out how the effect of flipped classroom on colleges’ writing ability of descriptive text for third semester at university of HKBP Nommensen Pematangsiantar. The experimental class achieved the best post-test score of 96 compared to the control class’ score 82.5. Using flipped classroom as a teaching model for writing descriptive text better than teaching writing without flipped classroom. The outcome of the t-test is 4.868. The value of 1.670 was derided by the researcher after referring to the t-table with significance level of 0.05. The t-test result shows that flipped classroom is affective in teaching descriptive text as indicated by the t-value surpassing the t-table value 1.671 at a significance level of 0.05. Ha has been admitted as meaningful, whereas Ho has been rejected. From the analysis, it can be conclude that the academic performance in writing of seventh grade students at University of HKBP Nommesen Pematangsiantar is substantially distinct between individuals who received instruction on writing using the flipped classroom compared to those who didn’t use flipped classroom. Based on the explanation above, it can be inferred that used the flipped classroom as learning model increase the descriptive text writing skills for third semester University of HKBP Nommesen Pematangsiantar.